The Influence of Learning Motivation Using the Project-Based Learning Model on Student Learning Outcomes in PKK Subjects at SMK Negeri 5 Padang. - Deri Syafamukmin Paderma; Fiki Efendi; Yufrizal A; Bulkia Rahim (Unversitas Negeri Padang, 2025)
The main problem in this research is: How does learning motivation using the Project Based Learning Model affect learning outcomes in Class XI PKK subjects at SMK Negeri 5 Padang. The aim of this research was designed to: measure the influence of learning motivation using the Project Based Learning model on learning outcomes in Class XI PKK subjects at SMK Negeri 5 Padang. In this research, researchers used quantitative research methods, namely correlational research. Correlational research is research used to find out the magnitude of the relationship between variables. The sample for the research carried out was 31 students in the Class XI PKK subject at SMK Negeri 5 Padang. This research aims to measure the influence of learning motivation using the Project-Based Learning model on learning outcomes, using questionnaire instruments and test sheets that are filled in before and after being given treatment. Descriptive analysis shows that the average student learning motivation score is in the high category, while the average learning outcomes are in the good category. Correlation between Learning Motivation and Learning Outcomes: The correlation value of 0.963 is greater than the r table of 0.355, which shows that there is a significant positive relationship between students' Learning Motivation and their learning outcomes. The conclusion from this research is that students' learning motivation has a significant relationship to their learning outcomes in implementing the Project-Based Learning model. Student learning motivation is proven to have a greater influence on learning outcomes.